It’s All about Edie, Stupid: Lessons from Litigating United States v. Windsor - Kaplan, Roberta A. (Columbia Journal of Gender and Law, 2015)
There is really only one thing that I know for sure. No human being knows what life has in store for them. My client Edie Windsor surely didn’t. As a young, middle-class woman growing up in Philadelphia after the Depression and World War II, she obviously had no idea what her future would hold. When asked shortly after we filed our case what it felt like to be a plaintiff, Edie remarked that it’s one thing to be “out” as a lesbian, but it’s another thing entirely to be the “out lesbian who just happens to be suing the United States of America.”